Comparison of two commercial solid‐phase microextraction fibers for the headspace analysis of volatile compounds in different pork and beef cuts. Issue 10 (12th October 2018) - Mansur, Ahmad Rois; Lee, Hyun Jun; Choi, Hyo‐Kyoung; Lim, Tae‐Gyu; Yoo, Miyoung; Jang, Hae Won; Nam, Tae Gyu
Abstract : The performance of carboxen/polydimethylsiloxane (Car/PDMS) and divinylbenzene/Car/PDMS (DVB/Car/PDMS) fibers in extracting volatile organic compounds (VOCs) from different pork and beef cuts by headspace solid‐phase microextraction (HS‐SPME) was compared. A principal component analysis (PCA), cluster analysis (CA), and an analysis of variance were employed subsequently to evaluate the extraction performance. DVB/Car/PDMS fibers exhibited similar VOC profiles, but were less effective than Car/PDMS fibers which showed significantly ( p < 0.05) higher extraction yields of major volatile groups including acids, alcohols, aldehydes, amines, and ketones in most of the tested meat cuts. There were no significant ( p > 0.05) differences in the amount of aliphatic hydrocarbon, aromatic hydrocarbon, esters, and sulfur compounds extracted by both fibers. Car/PDMS exhibited significant ( p < 0.05) differences in the amount of VOCs extracted from different meat cuts, while DVB/Car/PDMS fiber did not. These findings might provide insights into HS‐SPME of VOCs from different meat cuts. Practical applications: The application of HS‐SPME for the determination of VOCs in raw or processed meats, particularly pork and beef cuts, has been extensively studied in recent years. Among the commercial SPME fibers available, Car/PDMS and DVB/Car/PDMS fibers are the most frequently employed. However, no adequate information regarding the selection process and comparison of the fibers has been provided. The results of this study demonstrate that the profile of VOCs in different cuts of pork and beef was strongly influenced by the type of fiber used for extraction. Thus, these findings might provide new insights into the HS‐SPME analysis of VOCs in different meat cuts, especially the selection of fibers for the extraction of specific VOC analytes.